Time trends of overall survival and other outcomes in patients with mHSPC: An observational study of U.S. EHR data (TIMES). Issue 28 (1st October 2022) - Shore, Neal D.; McKay, Rana R.; Preston, Mark; Gregg, Justin R.; Salami, Simpa Samuel; Ross, Ashley; Bruno, Amanda; Srinivasan, Shankar; Ortiz, Jorge A.; Constantinovici, Niculae
Abstract : 403 Background: Metastatic hormone-sensitive prostate cancer (mHSPC) initially responds to androgen deprivation therapy (ADT), but unfortunately most patients (pts) develop metastatic castration-resistant prostate cancer (mCRPC) within 1–3 years. The CHAARTED trial showed a clear benefit of adding docetaxel (DTX) to ADT, improving median overall survival (OS) by 10.4 months (mo). ARASEC is a single-arm US study evaluating darolutamide + ADT in 200 pts with mHSPC, who will be matched using patient-level data to the ADT alone arm of CHAARTED. The TIMES study evaluated a potential time bias in treatment patterns and clinical outcomes in pts with mHSPC receiving therapy before or after the OS analysis of CHAARTED was reported. Methods: This retrospective study used Flatiron Metastatic Prostate Cancer Core Registry data from January 1, 2013, to June 30, 2020, divided into two cohorts: before and after June 30, 2016 (cohort 1 pre-CHAARTED; cohort 2 post-CHAARTED). Differences in OS and time to mCRPC were assessed using Cox proportional hazard models controlling for baseline characteristics, including age, initial mHSPC treatment, Gleason score, and time from prostate cancer diagnosis to mHSPC. The test for equivalence used hazard ratio (HR) confidence limits of 0.80 to 1.25 at a 2-sided 95% level. Results: Data from 9256 pts with mHSPC (cohort 1 4503; cohort 2 4753) were analyzed. Median age was 73 years in both cohorts. M1 status at initial diagnosis was 55% in cohort 1 and 60% in cohort 2. Other clinical characteristics and laboratory values were generally similar. mHSPC treatments are shown in the Table. Use of DTX or novel anti-hormonal agent (NAH) increased from cohort 1 to cohort 2. The percentage of pts receiving ADT alone or with other treatment (supportive care) remained essentially the same (25.7% and 26.5%, respectively), and no mHSPC treatment was identified for 32.9% and 21.7% of pts in cohorts 1 and 2, respectively. Median OS was 5.4 months longer for cohort 1 (43.7 mo) vs cohort 2 (38.3 mo). In multivariate analyses adjusting for baseline variables, cohort 2 had poorer survival, with an HR upper confidence limit outside the predefined limits for equivalence (HR 1.18; 95% CI 1.09, 1.28). The HR for time to mCRPC fell within the predefined limits (HR 1.16; 95% CI 1.09, 1.23). Conclusions: Changes in treatment patterns were observed following CHAARTED, but use of DTX or NAH increased only to 32%, despite level I evidence and guideline recommendations. Real-world mHSPC patient outcomes, which are influenced by multiple factors, have changed minimally during the past 5 years, suggesting that use of the CHAARTED ADT alone arm as a comparator for ARASEC has a low risk of historical time bias.Table. mHSPC treatment pre vs post CHAARTED. Treatment, % Pre (n = 4503) Post (n = 4753) DTX 10.5 13.9 NAH 1.6 18.3 1st-generation antiandrogen 29.3 19.6 ADT + other 11.6 11.6 ADT alone 6.5 8.9 Other 7.6 6.1 None/unknown 32.9 21.7